Relationship between Leaf Traits and PM-Capturing Capacity of Major Urban-Greening Species - Sanghee Park; Jong Kyu Lee; Myeong Ja Kwak; Yea Ji Lim; Handong Kim; Su Gyeong Jeong; Joung-a Son; Chang-Young Oh; Sun Mi Je; Hanna Chang; Kyongha Kim; Su Young Woo (Horticulturae, 2022)
High concentrations of airborne particulate matter (PM) in urban areas are of great concern to human health. Urban greening has been shown to be an effective and eco-friendly way to alleviate particle pollution, and attention to its role in mitigating particle pollution has increased worldwide. The species-specific PM-capturing capacity of ten urban-greening species in Seoul was evaluated by leaf functional traits (average leaf area (ALA), specific leaf area (SLA), and leaf width-to-length ratio (W/L)), microstructures (roughness, stomata, and trichomes), and physicochemical traits (contact angle (θw), surface free energy (rs), the work of adhesion for water (Wa), and epicuticular wax loads (EWL)). The relationships between leaf traits and PM adsorption by leaves were revealed by Pearson’s correlations and principal component analysis (PCA). A gravimetric method was used to quantify, by particle size, the PM adsorbed on leaf surfaces or embedded in leaf epicuticular wax layers. The key factors for PM adsorption on leaf surfaces were the SLA, the mean roughness value (Ra), and stomatal size. The SLA and Ra of adaxial leaf surfaces were negatively correlated with PM accumulation on leaf surfaces, while stomatal length and width were positively correlated with surface PM load. The rs and EWL positively affected the in-wax PM load. Species-specific PM deposition was the result of complicated mechanisms of various leaf traits. Three evergreen shrub species, Buxus sinica (Rehder & E.H. Wilson) M.Cheng var. insularis (Nakai) M.Cheng, Taxus cuspidata Siebold & Zucc., and Euonymus japonicus Thunb., were efficient in capturing both surface PM and in-wax PM. The PCA revealed that the high PM accumulation efficiency of these three species might be attributable to the interaction between stomatal size and EWL. Aesculus turbinata Blume, Chionanthus retusus Lindl. & Paxton, and Rhododendron schlippenbachii Maxim. had intermediate PM adsorption ability, which might be a result of interactions among stomatal density, the Wa of adaxial surfaces, and ALA. Magnolia denudata Desr., Styphnolobium japonicum (L.) Schott, Liriodendron tulipifera L., and Ginkgo biloba L. had low PM accumulation efficiency. These four species exhibited correlations among SLA, the Ra of adaxial leaf surfaces, and W/L, which had negative effects on PM adsorption.